2021
DOI: 10.14719/pst.2021.8.4.1181
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic potentials and pharmacological properties of Talinum triangulare (Jacq.) Willd. in the treatment and management of diabetes mellitus and other conditions

Abstract: There is a growing interest in the use of medicinal plants. Previously, the assumption was that the use of medicinal plants is peculiar to developing and poor nations. However, due to advances in technology, innovative and scientific research on medicinal plants, the trend has changed. The number of people using medicinal plants for various reasons has increased significantly in developed countries. Research studies have shown that several plants display antioxidant, antidiabetic, antimicrobial, anticancer and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 28 publications
(40 reference statements)
0
4
0
Order By: Relevance
“…The study demonstrated the efficacy of the extract in managing diabetes by inhibiting α ‐amylase and hydroxymethyl glutaryl CoA reductase, stimulating cellular uptake of glucose and regulating hepatic lipid synthesis [232] Another study found a reduction in fasting blood glucose of male albino rats (100–120g) when treated with the leaf extract (3 ml/100 g bw), which further indicates its hypoglycemic potential [96] . Various leaf extracts exhibiting considerable reductions in the level of blood glucose suggest their potential role in facilitating the release of insulin [228] …”
Section: Pharmacological Activitiesmentioning
confidence: 99%
See 2 more Smart Citations
“…The study demonstrated the efficacy of the extract in managing diabetes by inhibiting α ‐amylase and hydroxymethyl glutaryl CoA reductase, stimulating cellular uptake of glucose and regulating hepatic lipid synthesis [232] Another study found a reduction in fasting blood glucose of male albino rats (100–120g) when treated with the leaf extract (3 ml/100 g bw), which further indicates its hypoglycemic potential [96] . Various leaf extracts exhibiting considerable reductions in the level of blood glucose suggest their potential role in facilitating the release of insulin [228] …”
Section: Pharmacological Activitiesmentioning
confidence: 99%
“…[96] Various leaf extracts exhibiting considerable reductions in the level of blood glucose suggest their potential role in facilitating the release of insulin. [228] 8.6. Anti-tumor Activity…”
Section: Neuroprotective and Cognitivementioning
confidence: 99%
See 1 more Smart Citation
“…Waterleaf acts as green forage for cattle (Oguntibeju and Okaiyeto, 2021) in order to meet the unavailability of green fodder (Meena et al, 2018) in many regions especially during summer. Characteristics of Talinum fruticosum such as palatability, nutrient composition, fibre proportion, digestibility, etc.…”
Section: Talinum Fruticosum: a Potential Multi-value Plant: A Review ...mentioning
confidence: 99%
“…According to traditional medicine the leaves of T. triangulare are used to treat polyuria, inflammations, diuretic, stomach troubles, sore throat (Burkill, 1994;Khare, 2007), gastrointestinal disorders (Mensah et al, 2008), bacterial infections, diabetes mellitus (Aja et al, 2010;Eleazu and Eleazu, 2013), antidiabetic, hypoglycaemic, antiulcer, antimicrobial, antioxidant activities (Fasuyi, 2006), anti-inflammatory properties, high cholesterol, high kaempferol content, hypertension (Teugwa et al, 2013;Ijomone and Ekpe, 2016;Olorunnisola et al, 2016;Oguntibeju and Okaiyeto, 2021), hepatic ailments and cancer (Liang et al, 2011). It is also used to treat Shistosomiasis, scabies, fresh cuts, high blood pressure, anemia, stroke, obesity and can function as immune-stimulant (Mbang et al, 2008;Ogunlesi et al, 2010;Agbonon et al, 2010).…”
Section: Introductionmentioning
confidence: 99%